Pendidikan pranikah terhadap kesiapan menghadapi kehamilan pertama pada calon pengantin putri - Dewi Rokhanawati; Umu Hani Edi Nawangsih (Universitas Aisyiyah Yogyakarta, 2017)
Abstract: Pregnancy is the first phase of the reproductive cycle that needsto be prepared by the bride. At the time of pregnancy occurs share thechanges that will affect the physical and psychological condition of women.Objective: to determine the effect of premarital education preparednessfirst pregnancy at bride in KUA Region Bantul, Yogyakarta in 2014.Methods: Data were collected through questionnaires pre and posttest to43 bride chosen by accidental in September 2014. Analysis data by pairedt test. Results: show after educational intervention premarital decrease ofrespondents who are not ready to face the first pregnancy of 57.5% downto 39.5%. Premarital education affect the first pregnancy preparedness onthe bride at KUA Bantul district of Yogyakarta in 2014 (p value = 0.000).Suggestion: to KUA Bantul district is expected to cooperate with the localhealth center to revive the course program bride.